2007
DOI: 10.1207/s15402010bsm0501_1
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Self-Reported Sleep Disturbance and Environmental Noise Based on Reanalyses of Pooled Data From 24 Studies

Abstract: This study establishes functions that specify self-reported sleep disturbance in relation to the exposure to nighttime transportation noise, by reanalyzing pooled data from previous studies. Results are based on data from 28 original datasets obtained from 24 field studies (4 studies collected data regarding 2 sources) including almost 23,000 participants exposed to nighttime levels ranging from 45 to 65 dB. Functions are presented that give the percentage highly sleep disturbed, sleep disturbed, and (at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
123
3
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(148 citation statements)
references
References 9 publications
(10 reference statements)
13
123
3
2
Order By: Relevance
“…This suggests that the association in the full sample may have been diluted due to misclassification of total noise exposure from traffic. Although studies on railway noise and cardiovascular endpoints are lacking, adverse effects of railway noise, such as annoyance and sleep disturbance, are well-documented (55,56). Unfortunately, we lacked sufficient precision in the estimation of exposure to noise from railways, making it difficult to assess exposure-response relationships.…”
Section: Selander Et Almentioning
confidence: 99%
“…This suggests that the association in the full sample may have been diluted due to misclassification of total noise exposure from traffic. Although studies on railway noise and cardiovascular endpoints are lacking, adverse effects of railway noise, such as annoyance and sleep disturbance, are well-documented (55,56). Unfortunately, we lacked sufficient precision in the estimation of exposure to noise from railways, making it difficult to assess exposure-response relationships.…”
Section: Selander Et Almentioning
confidence: 99%
“…Urban noise is a major environmental problem, mainly due to intense road and air traffi c. Among the most important health effects of urban noise is sleep disturbance (1,2). Every third EU resident complains about sleep disturbed by night noise exceeding the level of 55 dB(A).…”
mentioning
confidence: 99%
“…In the literature, different indicators have been used to describe the effects of aircraft noise on sleep quality (Finegold, 2010). Most studies have considered nighttime (Lnight) noise exposure (Jones & Rhodes, 2013;Miedema & Vos, 2007), but some studies have shown that exposure to daytime noise can disrupt sleep (Fruhstorfer, Fruhstorfer, & Grass, 1984) and reduce sleep duration (Blois, Debilly, & Mouret, 1980). In the present study, day-evening-night, day-and night-time exposures to aircraft noise were estimated at the place of residence of the participants.…”
Section: Discussionmentioning
confidence: 99%